Betula_nana_only_structure-input - Eidesen, Pernille Bronken; Alsos, Inger Greve; Brochmann, Christian (Dryad Digital Repository, 2015)
Input file to the software program STRUCTURE based on the AFLP matrix only including B.nana ind(528) and 115 markers, 3 primer combinations